2016
DOI: 10.17586/2220-8054-2016-7-4-768-773
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and catalytic properties of silver nanoparticles loaded zeolite: green method for synthesis of silver nanoparticles using lemon juice as reducing agent

Abstract: Zeolite Y is a cage-like alumina silicate which is widely used as solid support to immobilize metal and metal sulfide nanoclusters. We have attempted to synthesis silver nanoparticle-loaded zeolite Y by an ion exchange method followed by a biogenic reduction method using lemon juice as a reducing agent. The antimicrobial activity of the silver ion, silver nanoparticles and silver chloride-modified zeolite was investigated against various Gram negative and Gram positive microorganisms. The silver nanoparticle-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…They found that the Cu/ Natrolite zeolite functional nanoparticles took only 30 min for N‐formylation of benzylamine with the yield of 94% which is higher than any other catalysts . Selvamuthumari et al., immobilized the Ag nanoparticles within zeolite‐Y by employing ion exchange method followed by the biogenic reduction process using lemon juice as a reducing agent for Ag 2+ ions. The obtained Ag nanoparticle functionalized zeolite‐Y showed excellent catalytic performance in reducing 4‐NP and antimicrobial activity against Bacillus subtilis and Salmonella typhi bacterias .…”
Section: Phytochemical Fabrication Of Functional Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the Cu/ Natrolite zeolite functional nanoparticles took only 30 min for N‐formylation of benzylamine with the yield of 94% which is higher than any other catalysts . Selvamuthumari et al., immobilized the Ag nanoparticles within zeolite‐Y by employing ion exchange method followed by the biogenic reduction process using lemon juice as a reducing agent for Ag 2+ ions. The obtained Ag nanoparticle functionalized zeolite‐Y showed excellent catalytic performance in reducing 4‐NP and antimicrobial activity against Bacillus subtilis and Salmonella typhi bacterias .…”
Section: Phytochemical Fabrication Of Functional Nanostructuresmentioning
confidence: 99%
“…Selvamuthumari et al., immobilized the Ag nanoparticles within zeolite‐Y by employing ion exchange method followed by the biogenic reduction process using lemon juice as a reducing agent for Ag 2+ ions. The obtained Ag nanoparticle functionalized zeolite‐Y showed excellent catalytic performance in reducing 4‐NP and antimicrobial activity against Bacillus subtilis and Salmonella typhi bacterias . Hatamifard and his co‐workers synthesised the functional Ag/zeolite nanostructures using Euphorbia prolifera leaf extract as the reducing agent for silver ions.…”
Section: Phytochemical Fabrication Of Functional Nanostructuresmentioning
confidence: 99%
“…To overcome these demerits, biogenic nanoparticles synthesized from plant extracts without making use of any poisonous chemicals would be considered attractive for nanotechnology. 10 The phytochemicals present in plants are water soluble and can cause the immediate reduction of metal ions. 11 A number of medicinal plants, such as Acorus calamus, Alternanthera dentate, Ocimum sanctum, Azadirachta indica, Brassica rapa, Coccinia indica, Vitex negundo, Solanum xanthcarpum, Croton bonplandianum, Andrographis paniculata, and Cleome viscosa, have been reported in literature for the synthesis of biogenic Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%